Unravelled facets of milk derived opioid peptides: a focus on gut physiology, fractures and obesity. (2nd January 2020) - Aslam, Hajara; Ruusunen, Anu; Berk, Michael; Loughman, Amy; Rivera, Leni; Pasco, Julie A.; Jacka, Felice N.
Abstract: Beyond being a source of key nutrients, bovine milk influences physiological functions by synthesising bioactive peptides during the process of digestion. Some of the claimed negative health outcomes associated with milk consumption, such as cardiovascular diseases and type 1 diabetes may be attributed to an opioid peptide, beta-casomorphin-7 (BCM-7), derived from A1 beta-casein. BCM-7 exerts its function by binding to the μ-opioid receptors in the body. It is hypothesised that activation of the μ-opioid receptors in the gut can alter gut microbial composition, impair gut barrier integrity and bile acid metabolism, in addition to increasing gastrointestinal transit time and gut inflammation. Further, it is hypothesised that BCM-7 may influence fractures and obesity via μ-opioid receptor pathways. In conclusion, it appears that BCM-7 might have multiple functions pertinent to human health; however, the evidence is limited and warrants further pre-clinical and clinical studies for hypothesis confirmation.